Comparison of efficacy and safety of topical versus intravenous tranexamic acid in total hip arthroplasty: A meta-analysis. Issue 36 (September 2016) - Li, Jian; Zhang, Zhijie; Chen, Jie
Abstract: Background: The study aimed to compare the effectiveness and safety of topical versus intravenous (IV) tranexamic acid (TXA) for reducing blood loss in primary total hip arthroplasty (THA). Methods: This systematic review and meta-analysis were performed according to the preferred reporting items for systematic reviews and meta-analyses statement criteria. PubMed, Embase, the Cochrane Library, Web of Science, Chinese Biomedicine Literature (CBM), Wanfang Database, China National Knowledge Infrastructure (CNKI), and Google Scholar were searched for randomized controlled trials (RCTs) and non-RCTs that compare topical versus IV-TXA administration for reducing blood loss during TKA from their inception to February, 2016. Meta-analysis was performed by Stata 12.0 software. Results: Seven studies comprising 2056 patients were included in this meta-analysis. No significant difference is found between topical TXA groups and IV-TXA groups regarding transfusion requirements (RR = 1.37, 95% confidence interval [CI]: 0.96–1.97, P = 0.083), total blood loss (MD 17.09, 95% CI: −33.74–67.91, P = 0.510), and hemoglobin decline (MD 0.32, 95%CI: −0.04–0.69, P = 0.122). Meanwhile, there is no significant difference in terms of the occurrence of deep venous thrombosis (RR = 1.09, 95% CI: 0.40–3.90, P = 0.869). Conclusion: Topical TXA has a similar efficacy to IV-TXA in reducing both blood loss and transfusion rate without sacrificing safety in primary THA.